Diet intake and adherence to recommendations in women with gestational diabetes mellitus - Saros, Lotta; Vahlberg, Tero; Pellonpera, Outi; Tertti, Kristiina; Laitinen, Kirsi (SPRINGERNATURE, 2025)
Background/objectives
Gestational diabetes mellitus (GDM) is best managed via lifestyle changes. We aimed at investigating to which extent women with GDM adhered to dietary recommendations and to which extent an impact was observed on the glycaemic control compared to women without GDM.
Subjects/methods
Women with overweight/obesity (n = 349) were recruited in early pregnancy. GDM was diagnosed with a 2-h oral glucose tolerance test in mid-or-early pregnancy (median 25.9 and 14.7 gestational weeks). Dietary assessments included an index of dietary quality (good >= 10 and poor < 10/15 scores) and 3-day food-diaries with nutrient intake calculated and dietary patterns identified. Glucose and insulin concentrations were analysed from blood samples collected in late pregnancy (after GDM diagnosis).
Results
Women with GDM (n = 98) followed more often a healthier dietary pattern (62.2%) than women without GDM (49.0%, p < 0.05), but no difference in good dietary quality was seen (53% vs. 59.8%, p = 0.071). While the majority of women with GDM adhered to some recommendations, 51% to carbohydrate, 54.1% to total fat and 69.4% to sucrose, only 16.3% adhered to the protein and 4.1% to the fibre intake recommendations. Women with GDM had lower adherence to protein, total fat and fibre recommendations but higher adherence to that of sucrose than women without GDM (p < 0.05). A good dietary quality was associated with lower insulin and HOMA2-IR values (p < 0.05).
Conclusions
Adherence to dietary recommendations, particularly fibre and protein intake, is unsatisfactory in women with GDM. Overall dietary quality is related to better control of glucose metabolism proposing a target for dietary counselling.